Constructing the Reproductive Behavior of Poor People: Regulating Procreation by Public Aid Recipients from Malthus to Murray - Tomczak, Stephen Monroe (Social Service Review, 2020)
0 citations (Crossref) [2023-10-31] WOS:000573596100002
Keywords: dept.swk; peer-reviewed

Community Collaboration for Social Workers - Tomczak, Stephen Monroe (Management and Leadership in Social Work: A Competency Based Approach, 2020)
The authors have had many years of leadership and management experience in a variety of settings and have discovered that there are few books that cover the majority of topics related to leadership and management specifically for social work education and practice. This book covers all the main areas of expertise required in a typical social work leadership and management experience. It incorporates all 21 competencies and 126 practice behaviors from the Network on Social Work Management (NSWM) and nine competencies and 29 practice behaviors espoused by the Council on Social Work Education (CSWE) and can serve as a textbook for social work programs at the graduate level. The book has many unique features. It provides a comprehensive list of leadership and management competencies from the NSWM and the CSWE along with a list of competencies and practice behaviors. The book presents leadership and management competencies and practice behaviors each chapter along with cases, examples, and activities of how to use them in practice situations. It discusses in detail the differences between management and leadership along with best management and leadership practices. The book provides examples of how to motive and successfully work with different age cohorts. It presents effective communication and marketing strategies. The book discusses in detail how to effectively work with groups and give examples of how to make meetings productive. It exhibits specific problem-solving and decision-making strategies along with examples. The book summarizes how to manage a range of organizational functions. It discusses the importance of collaborating with community groups and other stakeholders to succeed in making a difference. The book contains five parts that replicate the <abbrev>NSWM</abbrev>’s four domains of leadership: executive leadership in social work; resources management practices; strategic management and administrative skills for organizational growth and success; community collaboration; and supplemental materials.
Keywords: Leadership; Vocational qualifications; Social Work; dept.swk; faculty_collection; methods; Efficiency; Organizational; organization & administration; Leadership; Professional Competence; Personnel Management

Designing and Assessing Programs for Social Work - Tomczak, Stephen Monroe (Management and Leadership in Social Work: A Competency Based Approach, 2020)
The authors have had many years of leadership and management experience in a variety of settings and have discovered that there are few books that cover the majority of topics related to leadership and management specifically for social work education and practice. This book covers all the main areas of expertise required in a typical social work leadership and management experience. It incorporates all 21 competencies and 126 practice behaviors from the Network on Social Work Management (NSWM) and nine competencies and 29 practice behaviors espoused by the Council on Social Work Education (CSWE) and can serve as a textbook for social work programs at the graduate level. The book has many unique features. It provides a comprehensive list of leadership and management competencies from the NSWM and the CSWE along with a list of competencies and practice behaviors. The book presents leadership and management competencies and practice behaviors each chapter along with cases, examples, and activities of how to use them in practice situations. It discusses in detail the differences between management and leadership along with best management and leadership practices. The book provides examples of how to motive and successfully work with different age cohorts. It presents effective communication and marketing strategies. The book discusses in detail how to effectively work with groups and give examples of how to make meetings productive. It exhibits specific problem-solving and decision-making strategies along with examples. The book summarizes how to manage a range of organizational functions. It discusses the importance of collaborating with community groups and other stakeholders to succeed in making a difference. The book contains five parts that replicate the <abbrev>NSWM</abbrev>’s four domains of leadership: executive leadership in social work; resources management practices; strategic management and administrative skills for organizational growth and success; community collaboration; and supplemental materials.
Keywords: Leadership; Vocational qualifications; Social Work; dept.swk; faculty_collection; methods; Efficiency; Organizational; organization & administration; Leadership; Professional Competence; Personnel Management

The roots of social work practice - Tomczak, Stephen Monroe; Cross-Denny, Bronwyn (Health Science Faculty Publications, 2023)
Keywords: dept.swk

Macro-Level Social Work Interventions in Schools: Poverty Simulation Programs as Professional Development Opportunities for K–12 Educators - Curry, Anna Maria T.; Tomczak, Stephen Monroe (Children & Schools, 2023)
Num Pages: 7
Keywords: dept.swk

Appropriately Uncomfortable: A Conversation Among Three Colleagues About Structural Oppression Focusing on Racism and the Need for Action - Aguilar, Jemel; Smith, Carmela Fusciello; Tomczak, Stephen Monroe (Reflections: Narratives of Professional Helping, 2021)
In this reflection, three social work colleagues discuss three different perspectives on one statement about racism. We detail our emotionally challenging conversations about racism, microaggressions, and the meaning of social justice in social work to build a different bond and sense of understanding. We delve into how we understand each other, our differing viewpoints on the murders of Black people in American society such as George Floyd, and our perspectives on social workers’ relationships to social justice, racism, and social change in the context of the 2020 turmoil.
Number: 2
Keywords: dept.swk; higher education; oppression; peer-reviewed; racism; social work faculty

Teaching Note—Innovating the Curriculum: Bringing History Back Into Social Work Education - Abramovitz, Mimi; Curran, Laura; Harty, Justin S.; Toft, Jessica; Tomczak, Stephen Monroe (Journal of Social Work Education, 2024)
History, the major storehouse of information, informs us about the important relationship between people and society and increases our understanding of basic societal values and institutional arrangements. A recent New York Times op-ed described “The Dangerous Decline of the Historical Profession.” Likewise for historical content in social work education, exacerbated by the 1970s‘ rise of neoliberalism and the profession’s long marginalization of historical research and teaching. The Social Welfare History Group renews its call to bring historical content back into social work education and to correct its deep-seated race, class, gender, and colonizing distortions. To ensure that all social work courses include history, we can revive the value historical knowledge; prepare a cadre of historical researchers and instructors; financially support emerging scholars and develop a pipeline of history-informed faculty to teach the next generation of social workers.
_eprint: https://doi.org/10.1080/10437797.2023.2290481
Keywords: dept.swk; peer-reviewed

If Anti-Racism Is the Goal, Then Anti-Oppression Is How We Get There - Smith, Carmela Fusciello; Aguilar, Jemel P.; Kozu, Shuei; D'Angelo, Karen A.; Keenan, Elizabeth King; Tomczak, Stephen Monroe (Advances in Social Work, 2022)
Many schools of social work around the United States of America wrote anti-racism statements because of the recent murders of Black and Brown people. In this contribution, the authors describe a challenging and tense discussion of racism and anti-racism leading to a group process about oppression and anti-oppression in the social work profession. For some, the urgency to address racism led to tactics and strategies that got in the way of social workers engaging in anti-oppressive practices. While the structure of higher education often reinforces traditional hierarchies of power, the profession of social work calls us to promote our core values of social justice, integrity, and the importance of human relationships as we strive for an anti-oppressive future. Consequently, social work faculty may experience role conflict as we navigate these tensions. We believe it is important to harness and process such discomfort as we critically examine the power dynamics within our own department, and our own profession. This voluntary, ad hoc group, composed of a diverse group of faculty members, provides space for ongoing mutual aid, consciousness raising, appropriate discomfort, and accountability. If anti-racism is the goal, then anti-oppression is how we get there.
0 citations (Crossref) [2023-10-31] Number: 2
Keywords: White supremacy; dept.swk; peer-reviewed